There's no business like small business - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
From 30 November to 3 December 1999, CTA, together with CIRAD, the French Ministry for Foreign Affairs, and ENDA-Graf (Senegal), co-organised a seminar on small agrifood businesses in western and central Africa